Cell density-dependent regulation of microcystin synthetase genes (mcy) expression and microcystin-LR production in Microcystis aeruginosa that mimics quorum sensing - Shanlin Wang; Ping Ding; Siyu Lu; Pian Wu; Xiaoqian Wei; Ruixue Huang; Tianhan Kai (Ecotoxicology and Environmental Safety, 2021)
As the secondary metabolites of cyanobacterial harmful algal blooms (Cyano-HABs), microcystins (MCs) were generated under various environmental and cellular conditions. The understanding of the causes of MCs generation is of great interest in the field of water treatment and environmental science. In this work, we studied how Microcystis aeruginosa (FACHB-905) cell densities affect the MCs synthetase genes (mcy) expression, microcystin-LR (MC-LR) and quorum sensing molecules (Acyl-homoserine lactones (AHLs)) production. An electrochemical sensor was developed here for sensitive and quantitative detection of MC-LR that cultured at different cell densities. The results showed that mcy expression and MC-LR concentration started to increase when the cell density reached ca. 22 × 106 cells/mL, and was significantly increased with increasing cell densities. Moreover, the up-regulation of AHLs with increasing cell densities revealed that MC-LR is quorum sensing-mediated. Our results undoubtedly confirmed that MC-LR was produced in a cell density-dependent way that mimics quorum sensing, and the minimum cell density (ca. 22 × 106 cells/mL) that was required to produce MC-LR was provided and offered a reference standard for the prevention and control of MCs pollution in the actual water environment.